Ocean Acidification and Ocean Warming Effects on Pacific Herring (Clupea pallasi) Early Life Stages - Villalobos, Cristina; Love, Brooke A.; Olson, M. Brady (Frontiers in Marine Science, 2020)
Increasing green house gas emissions are expected to raise surface seawater temperatures and lead to locally intensified ocean acidity in the U.S. Pacific Northwest. Pacific herring (Clupea pallasi) are ecologically and economically important forage fish species native to this region. While the impacts of ocean acidification and ocean warming on organism physiology have been extensively studied, less is known on how concurrent climate change stressors will affect marine fish. Therefore, our study focused on the combined effects of ocean acidification and warming on Pacific herring early life history stages. Pacific herring embryos were incubated under a factorial design of two temperature (10°C or 16°C) and two pCO2 (600 µatm or 1200 µatm) treatments from fertilization until hatch (6 to 15 days depending on temperature). Elevated pCO2 was associated with a small increase in embryo mortality. Elevated temperature, as a single stressor, generated greater embryo mortality and embryo heart rates, larger yolk areas upon hatch, lower hatching success, and shorter larval lengths; compared with the same parameters measured under ambient temperature. The interaction of elevated temperature and pCO2 was associated with greater embryo heart rates and yolk areas compared to ambient conditions. This study suggests that while temperature is the primary global change stressor affecting Pacific herring embryology, interaction effects with pCO2 could introduce additional physiological challenges.